Pengaruh Kepemimpinan Otoriter, Motivasi dan Lingkungan Kerja Fisik terhadap Kinerja Karyawan Rumah Makan Apung Buana Badas - Alivia Chairani; Ahmad Jauhari; Nur Hidayati (Jurnal Manajemen dan Ekonomi Kreatif, 2024)
This research aims to determine the influence of the variables authoritarian leadership (X1), motivation (X2) and physical work environment (X3) on employee performance (Y) at the Buana Badas Floating Restaurant. This type of research is quantitative research. The data collection techniques used are primary data and secondary data. The sample selection used the saturated sampling method, the number of samples in the study was 39 respondents at the Buana Badas Floating Restaurant. This research data was obtained through questionnaires, interviews and literature studies. The analysis techniques used are Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression Analysis, T Test, F Test and Coefficient of Determination Test. The results of the research obtained the multiple linear regression equation Y= 10.762 + 0.0.277X1 + 0.392X2 + 0.652X3 and the t test results of the authoritarian leadership variable had a partially significant effect on employee performance with a sig result of 0.015 < 0.05. Motivation has a partially significant effect on employee performance with a sig result of 0.012 <0.05. The physical work environment has a partially significant effect on employee performance with a sig result of 0.000 < 0.05. The F test results obtained Fcount results with a significance value of 0.000 < 0.05. From the results of the analysis it can be concluded that authoritarian leadership, motivation and the physical work environment simultaneously and significantly influence the performance of Buana Badas Floating Restaurant employees.